If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 3)(4x + -1) = 0 Reorder the terms: 5(3 + 2x)(4x + -1) = 0 Reorder the terms: 5(3 + 2x)(-1 + 4x) = 0 Multiply (3 + 2x) * (-1 + 4x) 5(3(-1 + 4x) + 2x * (-1 + 4x)) = 0 5((-1 * 3 + 4x * 3) + 2x * (-1 + 4x)) = 0 5((-3 + 12x) + 2x * (-1 + 4x)) = 0 5(-3 + 12x + (-1 * 2x + 4x * 2x)) = 0 5(-3 + 12x + (-2x + 8x2)) = 0 Combine like terms: 12x + -2x = 10x 5(-3 + 10x + 8x2) = 0 (-3 * 5 + 10x * 5 + 8x2 * 5) = 0 (-15 + 50x + 40x2) = 0 Solving -15 + 50x + 40x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5'. 5(-3 + 10x + 8x2) = 0 Factor a trinomial. 5((-3 + -2x)(1 + -4x)) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(1 + -4x)' equal to zero and attempt to solve: Simplifying 1 + -4x = 0 Solving 1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = 0 + -1 -4x = 0 + -1 Combine like terms: 0 + -1 = -1 -4x = -1 Divide each side by '-4'. x = 0.25 Simplifying x = 0.25Solution
x = {-1.5, 0.25}
| 7x+15=6x+20 | | 0.25(4x-2)=x-.25 | | 4x+8y-2(7x-4y)= | | 63+8(6x-1)=7(6x+1) | | -8(b-862)=-560 | | 16=8c | | 2.50(m+15.00)=662.5 | | 2.5r=95 | | 6(3x-6)=10x | | a+3ab+6+7a-2ab-1=0 | | 75+5x=10x+100 | | 9b-7b+6=-4b+78-3b | | 11x-160=56-7x | | 10+58=6x+2 | | 2x^4+3x-50=0 | | 5a+4b-5(7a-9b)= | | 26w+20=956 | | X-2x=125 | | (1+y)x^2-3yx+(1-y)=0 | | 2.50(m+15.00)=412.5 | | 84=2x-4+2x+4 | | 75=4529 | | -1-10r^2=-881 | | 3.4=y+2.1 | | -3x^2+8x-6=0 | | -8p-8=-14-7p | | -2x+(-21)=23 | | -1-10r^2=881 | | 84=4x^2-8+8-16 | | 929=97+13r | | 31/2(6x-21/2)+51/3=-62/3(-3x+16/5)+122/3 | | -70=-2(n+5)+7(4-6n) |